2010
DOI: 10.1007/s11274-009-0303-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of oxytetracycline production after gamma irradiation-induced mutagenesis of Streptomyces rimosus CN08 strain

Abstract: Streptomyces rimosus CN08 isolated from Tunisian soil produced 8.6 mg l(-1) of oxytetracycline (OTC) under submerged fermentation (SmF). Attempts were made for enhancing OTC production after irradiation-induced mutagenesis of Streptomyces rimosus CN08 with Co(60)-γ rays. 125 OTC-producing colonies were obtained after screening on kanamycin containing medium. One mutant called Streptomyces rimosus γ-45 whose OTC production increased 19-fold (165 mg l(-1)) versus wild-type strain was selected. γ-45 mutant was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This result indicates that wheat bran is the most suitable substrate for producing FK506 in the TCM8594 strain, which may have been due to the fact that wheat bran contains sufficient nutrients and remained loose under moist conditions, thereby creating a large surface area (Babu and Satyanarayana 1995). It was previously reported that wheat bran helped to produce the highest titers of tylosin, meroparamycin, and oxytetracycline (El-Naggar et al 2009;Khaliq et al 2009;Lazim et al 2010). However, the wild-type strain produced a very small amount of FK506 during SSF, using five substrates (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…This result indicates that wheat bran is the most suitable substrate for producing FK506 in the TCM8594 strain, which may have been due to the fact that wheat bran contains sufficient nutrients and remained loose under moist conditions, thereby creating a large surface area (Babu and Satyanarayana 1995). It was previously reported that wheat bran helped to produce the highest titers of tylosin, meroparamycin, and oxytetracycline (El-Naggar et al 2009;Khaliq et al 2009;Lazim et al 2010). However, the wild-type strain produced a very small amount of FK506 during SSF, using five substrates (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 80%
“…However, Kota and Sridhar (1998) reported that production of cephamycin C reached a maximum on day 15 in SSF. Lazim et al (2010) also reported that oxytetracycline production reaches its maximal value on day 5. This result indicates that optimal production of secondary metabolites depend on the growth kinetics of the microbes.…”
Section: Effect Of Incubation Temperaturementioning
confidence: 90%
“…Successful formation of protoplasts from several different strains has been demonstrated previously [11][12][13][14][15]. We found that even the fresh mycelia of routine culture of Streptomyces rimosus JH was difficult to form protoplast, so the addition of glycine in culture medium YM and the lysozyme concentration for protoplast formation were optimized.…”
Section: Protoplast Preparation Ntg Mutagenesis and Screening Of Higmentioning
confidence: 86%
“…Moreover, Shahbazi et al (2014) stated that a mutant strain of Trichodermareesei irradiated at 250 Gy of gamma ray (PTCC 5142) showed the maximum production of cellulose enzyme compared with UV-irradiated mutant and wild-type strains [21]. The tremendous increase was also reported with oxytetracycline production from a Streptomyces rimosus CN08 mutant which was called Streptomyces rimosus γ-45 [22]. Besides, a 12 fold increase was reported in the production of epsilon-pyrromycinone glycosides in Streptomyces galilaeus with respect to the wild strain after both natural selection and treatment with mutagens as gamma-irradiation [23].…”
Section: Discussionmentioning
confidence: 99%